(untitled) (Scientific journal of the Fergana State University, 2024)
Each preparation applied to the soil must be cost-effective and used taking into account the properties and characteristics of the soil. Not all forms of silicon present in the soil are suitable for absorption by plants, when silicon is absorbed from the root to the stem in the form of a mobile one, i.e., monosilicic acid (H4SiO4), through special transporter genes in plant tissue (Ma et al., 2011). The purpose of this study was to evaluate the positive effect of silica preparations on live weight and enzymatic properties of soil. This study examined seasonal changes in the activity of the enzymes peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL) on soil enzymes in the field crop field “Avez Mirshod Rustam”, Bukhara district of Bukhara region. Seasonal changes in the activity of enzymes were studied under the influence of preparations-Aminosid-Aton, Aminosid-Silicon, Bionitrogen.